2011
DOI: 10.1152/ajpcell.00433.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AQP2 localization by S256 and S261 phosphorylation and ubiquitination

Abstract: Vasopressin-induced water reabsorption coincides with phosphorylation of aquaporin-2 (AQP2) at S256 (pS256), dephosphorylation at S261, and its translocation to the apical membrane, whereas treatment with the phorbol ester 12-tetradecanoylphorbol-13-acetate (TPA) induces AQP2 ubiquitination at K270, its internalization, and lysosomal degradation. In this study we investigated the relationship between S256 and S261 phosphorylation in AQP2 and its ubiquitination and trafficking in MDCK cells. Forskolin stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 44 publications
5
79
2
1
Order By: Relevance
“…Tamma et al found that the cAMP/PKA-dependent S261 phosphorylation also occurs in the AQP2-S256A mutant, which cannot be phosphorylated at S256, and that forskolin induces dephosphorylation of S261 in this mutant. 18 However, our data seem in contrast to studies by Hoffert and coworkers, who had observed that cAMPstimulated and PKA-dependent phosphorylation of S256 precedes and primes for phosphorylation of S269. 15 The reason for the discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Tamma et al found that the cAMP/PKA-dependent S261 phosphorylation also occurs in the AQP2-S256A mutant, which cannot be phosphorylated at S256, and that forskolin induces dephosphorylation of S261 in this mutant. 18 However, our data seem in contrast to studies by Hoffert and coworkers, who had observed that cAMPstimulated and PKA-dependent phosphorylation of S256 precedes and primes for phosphorylation of S269. 15 The reason for the discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…12 AVP mediates dephosphorylation of S261. 15,18 This is associated with decreased polyubiquitination and proteasomal degradation and an enhanced AQP2 abundance, which contributes to the increase in water reabsorption of the collecting duct in response to AVP. 19 Although several proteins controlling AQP2 trafficking were identified and the paths of AQP2 to and from the plasma membrane are defined in general terms, 1,17 the molecular details underlying AQP2 trafficking are unclear.…”
mentioning
confidence: 99%
“…As reported, 34 addition of the prostaglandin synthesis inhibitor indomethacin was needed to reduce basal cAMP and AQP2-pS256 levels 12,34 and was present in all treatments.…”
Section: Cell Culture and Treatmentssupporting
confidence: 56%
“…Although vasopressin increases S264 and S269 phosphorylation, it decreases S261 phosphorylation. [9][10][11][12] Regarding the potential kinases responsible for the phosphorylation of these sites, c-Jun N-terminal kinase, p38, and cyclin-dependent kinases (cdks) cdk1 and cdk5 can phosphorylate AQP2 peptides at S261 in vitro. 13,14 Here, in the attempt to investigate the potential involvement of cdks in AQP2 regulation, we discovered a new PKA-independent signal transduction pathway regulating AQP2 phosphorylation and localization.…”
mentioning
confidence: 99%
“…The C-terminal 15 amino acids of AQP2 contain a vasopressin-regulated poly-phosphorylated region with four phosphorylated serine residues at S256, S261, S264 and S269 (T in human) (Hoffert et al, 2006). These sites have differing roles for regulation of channel function and localization (see, for example, Fushimi et al, 1997;Hoffert et al, 2008;Kamsteeg et al, 2000;Moeller et al, 2011;Moeller et al, 2010;Nedvetsky et al, 2010;Tamma et al, 2011). It has been proposed that phosphorylation of AQP2 results in increased accumulation of AQP2 on the plasma membrane owing to reduced internalization (Lu et al, 2007;Moeller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%